1999
DOI: 10.1046/j.1365-2486.1998.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of UV‐B radiation on the response of Norway spruce and Scots pine to ambient ozone concentrations

Abstract: Elevated levels of both ozone and UV-B radiation are typical for high-altitude sites. Few studies have investigated their possible interaction on plants. This study reports interactive effects of O3 and UV-B radiation in four-year-old Norway spruce and Scots pine trees. The trees were cultivated in controlled environmental facilities under simulated climatic conditions recorded on Mt Wank, an Alpine mountain in Bavaria, and were exposed for one growing season to simulated ambient or twice-ambient ozone regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Reactive surface compounds might also contribute to the varying ozone sensitivity of different conifer species (Schnitzler et al, 1999;Landolt et al, 2000) when exposed to the same cumulative ozone concentrations under light conditions. We anticipate therefore that surface ozonolysis plays an important role for the ozone tolerance of certain conifer species, too.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive surface compounds might also contribute to the varying ozone sensitivity of different conifer species (Schnitzler et al, 1999;Landolt et al, 2000) when exposed to the same cumulative ozone concentrations under light conditions. We anticipate therefore that surface ozonolysis plays an important role for the ozone tolerance of certain conifer species, too.…”
Section: Discussionmentioning
confidence: 99%
“…An alpine climate was simulated in the exposure chambers ( Thiel et al 1996 ) at GSF‐National Research Center for Environment and Health, according to data obtained at the Wank mountain near Garmisch‐Partenkirchen, Germany, at an elevation of 1170 m a.s.l. in the summer of 1990 ( Schnitzler et al 1999 ). Two‐hour means of half‐hourly measurements were used to simulate ambient ozone conditions in the exposure chambers.…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the interaction of elevated ozone concentrations and UV‐B radiation at the molecular level ( Thalmair et al 1996 ; Zinser, Ernst & Sandermann 1998). Furthermore, reports of interactive effects on trees, using simulated outdoor conditions, are likewise rare ( Zeuthen et al 1997 ; Baumbusch et al 1998 ), and it has been shown that UV‐B radiation can ameloriate some detrimental effects of ozone ( Schnitzler et al 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the effects of UV‐B radiation on coniferous tree species (Krupa & Kickert 1989; Sullivan & Teramura 1992; Schnitzler et al 1999). In Loblolly pine, enhanced UV‐B radiation had minimal effects on different parameters of photosynthesis (stomatal conductance, chlorophyll concentration, or quantum yield efficiency of photosystem II) (Sullivan & Teramura 1992; Naidu et al 1993).…”
Section: Introductionmentioning
confidence: 99%